Mentoring for assessment and adaptation programs for the curriculum in Inclusive Education: Pendampingan Asesmen dan Program Adaptasi Kurikulum Pendidikan Inklusif - suharsiwi*, suharsiwi; Pandia, Weny Savitry Sembiring; Yumna, Laila (Universitas Lancang Kuning, 2025)
This article examines the effectiveness of training and mentoring in curriculum assessment and adaptation programs for children with special needs at the elementary school level. The purpose of the community service is to describe teachers' abilities in assessing and adapting the curriculum and to evaluate the impact of ongoing mentoring on the implementation of an inclusive curriculum. The method used is ABCD (Asset Based Community Development), with an established framework for empowering the community. The findings of this community service activity indicate that effective training and mentoring can improve teachers' skills in curriculum assessment and adaptation, and have a positive impact on the learning process of children with special needs